A Straightforward Synthesis of Functionalized cis-Perhydroisoquinolin-1-ones - Federica Arioli; Maria Pérez; Celeste Are; Elies Molins; Joan Bosch; Mercedes Amat (Molecules, 2019)
Base-catalyzed annulation reactions of 5,6-dihydro-2(1H)-pyridones with Nazarov-type reagents are reported. The effect of the solvent polarity and the concentration of the reagents is studied. The process involves two successive Michael additions and stereoselectively provides functionalized cis-perhydroisoquinolin-1-ones.